2019
DOI: 10.1515/bmt-2019-0062
|View full text |Cite
|
Sign up to set email alerts
|

Effective brain connectivity estimation between active brain regions in autism using the dual Kalman-based method

Abstract: Brain connectivity estimation is a useful method to study brain functions and diagnose neuroscience disorders. Effective connectivity is a subdivision of brain connectivity which discusses the causal relationship between different parts of the brain. In this study, a dual Kalman-based method is used for effective connectivity estimation. Because of connectivity changes in autism, the method is applied to autistic signals for effective connectivity estimation. For method validation, the dual Kalman based method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 60 publications
(113 reference statements)
1
1
0
Order By: Relevance
“…In the study on effective connectivity of ASD, Rajabioun et al (2020) found that in the resting state, the effective connectivity between active areas of children with ASD reduced, which was consistent with the results of reduced effective connectivity of children with ASD in this paper. In addition, we found that the effective connection from ANG_R of DMN to PreCG_L of SMN and ADOS_G_STEREO_BEHAV score had significant negative correlation.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the study on effective connectivity of ASD, Rajabioun et al (2020) found that in the resting state, the effective connectivity between active areas of children with ASD reduced, which was consistent with the results of reduced effective connectivity of children with ASD in this paper. In addition, we found that the effective connection from ANG_R of DMN to PreCG_L of SMN and ADOS_G_STEREO_BEHAV score had significant negative correlation.…”
Section: Discussionsupporting
confidence: 90%
“…Effective connectivity has been defined as the effect of neurological activity in one brain region on another brain region. Unlike functional connectivity, effective connectivity can estimate the direction of information transfer of neural activity ( Rajabioun et al, 2020 ), which helps to understand the brain mechanisms behind neural activity. Dynamic causal modelling (DCM) ( Friston et al, 2003 ) is a common approach to effective connectivity.…”
Section: Introductionmentioning
confidence: 99%